EVALUASI PROGRAM WIRA WIRI DALAM PELAYANAN TRANSPORTASI PUBLIK DI KOTA SURABAYA - mahardani febrihapsari; amirul mustofa; Desak Gede suasridewi; Erlyna Hidyantari Hidyantari; Hardiono hardiono; Wiwik Prihartanti (Universitas Riau, 2026)
Congestion is one of the problems faced by big cities that is still cannot be solved. The Wira Wiri program is one of the solutions provided by the Surabaya city government to overcome congestion in the city. This research aims to conduct an evaluation analysis wira wiri feeder program in public transportation services in Surabaya city. This research uses a qualitative approach with the evaluation theory of William N Dunn's evaluation theory with 6 criteria namely effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. The data collected was then analyzed by using data analysis techniques from Miles and Huberman. Research implications shows that the Surabaya wira wiri feeder program has been running well, although some indicators show results that are not yet optimal. Responsiveness and accuracy indicators show a good degree because the feeder program is in accordance with the policy objectives. The feeder program is in accordance with the policy objectives of the feeder itself. While the indicators of effectiveness, efficiency, adequacy and equity show a good degree but still not optimal for several reasons, namely that there are areas that have not been covered by the feeder and the arrival schedule is not suitable due to unpredictable road conditions. Recommendations for the development of this program are the development of human resources, especially in terms of service, socialization of the wira wiri feeder to the community so that people are more familiar with the feeder as public transportation, increasing intermodal integration and increasing the number of units.